FOREIGN EXPERIENCE IN THE FORMATION OF SOCIAL PROTECTION INSTITUTIONS - Bobonov N. X. (Ecomind Press, 2025)
This article analyzes the experience of foreign countries in the formation of social protection institutions. By examining the social policy models of countries such as Sweden, Germany, and the United States, the study explores the main features, advantages, and disadvantages of various national social protection systems. The author compares the social-democratic model of Scandinavian countries, the conservative approach of European states, and the liberal model implemented in the United States, and proposes suitable approaches for Uzbekistan. The article also examines the role of international organizations such as the UN and ILO, as well as the influence of economic development, cultural values, and political structures. The author emphasizes the importance of adapting foreign experience to local conditions in order to develop an effective and sustainable system of social protection.
Keywords: Social protection, foreign experience, institutional model, social-democratic approach, conservative system, liberal model, Swedish experience, German model, American model, social insurance, state policy, international organizations.